Effects of different light quality and GA3 concentration on tobacco seedling growth, root characteristics, and carbon and nitrogen metabolism - Lei, Yafang; Cui, Zhiyan; Wang, Pingping; Ai, Suilong; Begum, Naheeda; Ahanger, Muhammad Abass; Zhang, Lixin (International Journal of Applied and Experimental Biology, 2023)
Light quality and gibberellins affect growth, development and morphogenesis of plants. In order to improve the quality of tobacco seedlings under greenhouse conditions, the influence of different light sources and their interaction with foliar-applied gibberellic acid (GA3) on key growth and metabolic parameters in tobacco were examined. Light sources included white, red and blue lights while GA3 was applied in three concentrations, i.e., 0, 50 and 100 mg L-1. The survival rate of the seedlings was observed after transplanting. Morphological parameters like plant height, stalk diameter, and length, width and number of leaves increased maximally with higher concentration of GA3 under all three light regimes, however, light sources did not show any visible difference. Further, root vitality, chlorophyll content and the activities amylase and nitrate reductase increased significantly due to GA3 application and achieved highest values with blue light + 100 mg L-1 GA3. Supplementation of red and blue light along with foliar application of GA3 significantly increased the growth parameters including seedling height, stem diameter, root-shoot ratio, leaf length and root vitality. The contents of carbon metabolites including starch, soluble sugars, and reducing sugars improved significantly in plants grown under red and blue lights in combination with foliar application of GA3. The results of the present study depict that growing tobacco under blue light and the application GA3 is beneficial in terms of achieving increased growth, root characteristics, carbon and nitrogen metabolism of tobacco seedlings.